INTERNALISASI PENDIDIKAN KARAKTER DI LEMBAGA KESEJAHTERAAN SOSIAL ANAK (LKSA) PANTI ASUHAN PUTRA ‘AISYIYAH - Hasrinal (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study discusses the internalization of educational character in the Child Welfare Institution (LKSA) Putra '‘AisyiyahOrphanage, the focus of the study is on efforts to develop religious character, independence, responsibility, discipline, mutual cooperation and appreciate the achievements of children living in orphanages. Character education is very important for children who often face emotional and social challenges due to the loss of their biological family environment. Through a systematic approach, this study aims to describe and analyze the objectives, strategies, and processes of implementing character education in the orphanage. The method used is descriptive with a qualitative approach, including observation and interviews with orphanage caregivers. The results of the study indicate that the process of internalizing character values ​​is carried out through structured daily activities, such as congregational prayer and independent tasks, which help children develop strong character and personality. This study is expected to provide theoretical contributions in the development of science and practically as a guide for caregivers in improving the care system and internalization of character education values. Overall, this study emphasizes the importance of the orphanage environment in supporting the development of children's character as a future generation who are not only academically intelligent but also have high faith, morals and social